CLINICAL INDICATORS OF FEEDING SELF-CARE DEFICIT BASED ON BARTHEL INDEX MEASUREMENT IN PATIENTS SUFFERING FROM STROKE - Intansari Nurjannah; Vini Febriyani Zulfa; Dwi Harjanto; Erna Fitriana; Ngatini Ngatini (Belitung Raya Foundation, Indonesia, 2017)
Objective: This aim of this research is to describe clinical indicators of feeding self-care deficit based on Barthel Index measurement in patients with stroke. Methods: The research used a quantitative description study with cross-sectional design. This research was conducted in one hospital in Yogyakarta, Indonesia on March – April 2017 with total sampling technique. Instrument was developed based on clinical indicators of NANDA-I nursing diagnosis of feeding self-care deficit. Results: There were 28 respondents involved in this study, with males (60.7%) and females (39.3%) with an average age of 57 years. Respondents who suffered from non-hemorrhagic stroke were 60.7% and hemorrhagic stroke were 39.3%. Clinical indicator items for impaired ability to swallow sufficient amount of food (9.1%) was found in respondents with independency criteria on Barthel Index. Impaired ability to swallow sufficient amount of food item (25%) and impaired ability to prepare food (25%) were found in respondents with partial dependency criteria. The most items identified on respondents with severe dependency criteria were impaired ability to self-feed a complete meal item (53.8%) and impaired ability to prepare food item (53.8%). Conclusion: There were different pattern of clinical indicators items found in different level of Barthel index level criteria.